Sick leave after arthroscopic meniscus repair vs. arthroscopic partial meniscectomy - Fredrik Boric-Persson; Aleksandra Turkiewicz; Paul Neuman; Martin Englund (Osteoarthritis and Cartilage Open, 2023)
Objective: To evaluate sick leave after meniscal repair vs arthroscopic partial meniscectomy (APM) and, for comparison, vs the general population. Method: Using Swedish register data we included all employed persons aged 19–49 years in the general population of Skåne region and identified those having had meniscus repair or APM in the period of 2005–2012. We retrieved data on sick leave during 1 year before until 2 years after surgery. We used logistic regression to estimate the risk differences of being on sick leave and negative binomial model to analyze differences in the number of days on sick leave. Results: We included 192 persons with meniscus repair, 2481 with APM, and 376 ​345 references without meniscus surgery. Of these, 55% of meniscus repair group, 43% of APM group had any sick leave in the 2-year period following the surgery, while 17% of the references were on sick leave in the corresponding period. The mean (SD) number of days of sick leave after meniscus repair was 55 (77) days and for APM 37 (86) days. Meniscus repair was associated with higher probability of sick leave compared to APM with an adjusted risk difference of 0.13 (95% CI 0.07–0.19). Conclusion: Persons undergoing meniscus repair have more frequent and 37% longer periods of sick leave in the short term than persons undergoing APM. However, sick leave in the long-term warrant further attention as successful repair may be associated with less knee osteoarthritis development than APM.